Skin-homing basophils and beyond - Shibuya, Rintaro; Kim, Brian S. (Frontiers in Immunology, 2022)
Basophils have been implicated in type 2 inflammation and numerous disorders in the skin such as helminth infection, atopic dermatitis, and urticaria. Although similar in form and function to tissue-resident mast cells, classical studies on basophils have centered on those from the hematopoietic compartment. However, increasing studies in tissues like the skin demonstrate that basophils may take on unique characteristics by responding to unique developmental, chemotactic, and activation cues. Herein, we highlight how recent studies in barrier immunology suggest the presence of skin-homing basophils that harbor a unique identity in terms of phenotype, function, and motility. These concepts may uniquely inform how basophils contribute to diseases at multiple epithelial surfaces and our ability to therapeutically target the innate immune system in disease.